Seasonality and Generalist Plant Resource Use Drive Bee Community (Hymenoptera, Apidae) composition in herbaceous restinga and dune environments - Allison Leandro Tietz; Denise Monique Dubet da Silva Mouga (Sociobiology)
Few bee inventories have investigated the interaction between bees and plants in the restinga in Santa Catarina State, a highly anthropized coastal environment, due to its value. In this context, in the southern coastal region of the State, the bee community and their foraging resources were ecologically analyzed, aiming to obtain data that support their conservation. For sampling, bees were collected over one year in herbaceous restinga and Laguna (SC) dunes, using entomological nets, trap dishes, and aromatic baits. The bees and plants were prepared, identified, and quantified. Ecological indices were calculated. Eighteen species of bees and sixteen species of associated plants were found. The collector’s curve stabilized, and richness estimators indicated a possible richness of 21.57 to 26.25 species. The five subfamilies of bees occurring in Brazil were found, with Halictinae having the highest richness and Apinae having the greatest abundance. Andreninae showed only one species (Callonychium luteimaculatum), as abundant as Apis mellifera. The plants most visited in terms of bee diversity are typical of the restinga and are highly attractive to bees. The periods with the highest results were spring and summer. The variation in temperature and the increase in plant richness increased bee abundance and richness, highlighting the region’s seasonality. The bee community showed a conservative generalist condition, which is favorable for species living in inhospitable conditions, providing moderate robustness. Due to the lack or absence of nesting resources, the studied bee community appears to originate from nearby adjacent areas.